Hematopoietic stem cell transplantation for pediatric acute myeloid leukemia patients with KMT2A rearrangement; A nationwide retrospective analysis in Japan. (December 2019) - Miyamura, Takako; Kudo, Kazuko; Tabuchi, Ken; Ishida, Hiroyuki; Tomizawa, Daisuke; Adachi, Souichi; Goto, Hiroaki; Yoshida, Nao; Inoue, Masami; Koh, Katsuyoshi; Sasahara, Yoji; Fujita, Naoto; et al.
Highlights: Three-year OS and DFS rates of KMT2A -rearrageged pediatric AML was 52.1% and 46.7%. Complete remission at HSCT was the most significant prognostic factor. Supportive therapy and considering donor source might improve treatment outcomes. Abstract: Objective: Pediatric acute myeloid leukemia (AML) with KMT2A rearrangement is detected in 15–20% of all pediatric AML patients and is associated with adverse outcomes even after allogeneic hematopoietic stem cell transplantation (HSCT). To investigate outcomes and prognostic factors, we investigated 90 pediatric AML patients with KMT2A rearrangement after allogeneic HSCT. Methods: We retrospectively analyzed Japanese registration data for patients who had received allogeneic HSCT between 1988 and 2011. Median age was 3 years (range, 0–15 years), and no gender difference was evident. Median observation period was 119 months. Results: The 3-year overall survival (OS) rate of KMT2A -rearranged AML was 52.1% (95% confidence interval (CI), 42.4–64%, n = 90), and the 3-year disease-free survival (DFS) rate was 46.7% (95%CI, 36.8–58.2%). The 3-year DFS of KMT2A -rearranged AML was not significantly poorer than that of other AML ( P  = 0.09), and no significant difference was also seen in 3-year OS rate ( P  = 0.21). Multivariate analysis showed disease status (complete remission) at HSCT was associated with better outcomes. A significant difference in treatment-related mortality (TRM) was apparent between HSCT from a HLA full-matched related donor and that from a haploidentical donor ( P  = 0.001). Discussion: HSCT is a curative option for pediatric AML with KMT2A rearrangement. Pretransplant status was the most significant prognostic indicator for relapse and survival. Enhancing supportive therapy to reduce TRM will further improve treatment outcomes of KMT2A -rearranged pediatric AML.